(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Now-a-days all public sector banks manage their customer through e-banking services. At present management of customers is a challenging job to the bankers. Without the e-CRM services the bank employees face very difficult to manage the customers and also provide better services. Father of our nation Mahatma Gandhi said that the success or failure of any business is in the hands of customers. So e-CRM services are more helpful to public sector bank employees not only to keep the existing customer for a longer period but also inviting a new customer for every moment. In traditional banking, bankers are manually do all the transactions work. So this manual process takes long time to process the single transactions, customers also wait in hourly basis. Some of the banks lose their customers, it affects the banking business. The e-CRM is to be solving all the problems. For that reasons all banks are implemented the e-CRM technologies. This technology does all the banking business within minutes. So the researcher wants to study the opinion of employees about e-CRM services in Virudhunagar District. In this study covers only the opinion of employees of Public sector banks